2020
DOI: 10.1093/rheumatology/keaa693
|View full text |Cite
|
Sign up to set email alerts
|

Endotypes of primary osteoarthritis identified by plasma metabolomics analysis

Abstract: Objective To identify endotypes of osteoarthritis (OA) by a metabolomics analysis. Methods Study participants included hip/knee OA patients and controls. Fasting plasma samples were metabolomically profiled. Common factor analysis and K-means clustering were applied to the metabolomics data to identify the endotypes of OA patients. Logistic regression was utilized to identify the most significant metabolites contributing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Sonh et al showed that several cytokines were elevated in synovial fluid and serum of patients with OA compared with normal samples when looking at an average level; however, it was also obvious that the pattern was very heterogeneous 38. Werdyani et al identified three distinct endotypes using metabolomics 39. One of those clusters showed some association with muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Sonh et al showed that several cytokines were elevated in synovial fluid and serum of patients with OA compared with normal samples when looking at an average level; however, it was also obvious that the pattern was very heterogeneous 38. Werdyani et al identified three distinct endotypes using metabolomics 39. One of those clusters showed some association with muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, OA has been recognized as a whole-organ disorder affecting various joint tissues in different degrees depending on the disease stage or the specific patient phenotype and endotype [28]; novel insights are anticipated using high-throughput OMIC technologies [29]. Moreover, OA is not a single entity, and current research focuses on personalized OA management according to OA subtypes and main drivers of disease progression [30].…”
Section: Discussionmentioning
confidence: 99%
“…For validation purposes, fasting plasma samples were derived from the Newfoundland and Labrador cohort in which the controls were from the Complex Diseases in Newfoundland population: Environment and Genetics (CODING) [ 35 ] and the OA samples from the Newfoundland Osteoarthritis Study (NFOAS; https://www.med.mun.ca/NFOAS/Home.aspx ) [ 36 ]. Plasma samples were from 20 controls and 20 OA, the latter equally divided into OA-obese ( n =10) and OA-non-obese ( n =10).…”
Section: Methodsmentioning
confidence: 99%